Developmental Ethics - EMINA, Kemi Anthony (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This essay delineates the key concerns of development ethics, focusing particularly on issues related to the recognition, distribution, and equity of costs and risks. The analysis extends to how these concerns manifest in the environmental impacts of economic development and explores ongoing efforts in human security analysis, aiming to integrate crucial development ethics considerations into a framework conducive to policy-relevant research and design. The essay contends that the development ethics agenda encompasses the examination of human costs, choices, and trade-offs in socioeconomic development processes, applying not only to events and choices in a geographically distinct ‘South’ and its interactions with the ‘North’ but also to global events and relations within the North. It emphasises the essential role of ethics throughout the research and policy formulation stages, advocating for early involvement to address issues related to the rights and interests of poor and vulnerable populations. The argument draws parallels with the World Social Science Report 2013, which underscores the necessary engagement of social sciences at all stages of environmental change research. Failing to incorporate ethical considerations at every stage risks neglecting the rights and interests of marginalised groups, allowing privileged interests to implicitly take precedence. The essay proposes human security analysis as a pertinent framework for posing critical questions and assessing threats to the fulfilment of needs for specific groups, especially the poor. The ethical role involves supporting responsible science that prioritises the lives of the poor and the most vulnerable while advocating for responsible development practices.